2020
DOI: 10.1021/acschembio.0c00439
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated Chondroitin Sulfate 9–18 Oligomers Exhibit Molecular Size-Independent Antithrombotic Activity while Circulating in the Blood

Abstract: Fucosylated chondroitin sulfate (FCS) oligosaccharides extracted from sea cucumber and depolymerized exhibit potent anticoagulant activity. Knowledge of the antithrombotic activity of different size oligosaccharides and their fucose (Fuc) branch sulfation pattern should promote their development for clinical applications. We prepared highly purified FCS trisaccharide repeating units from hexasaccharide (6-mer) to octadecasaccharide (18-mer), including those with 2,4-disulfated and 3,4-disulfated Fuc branches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…One experiment indicated that even if the patterns of sulfation differed, chondroitin sulfate obtained similar antithrombotic activity; thus, the influence of the chondroitin sulfation pattern could be less than the molecular weight with regard to the antithrombosis and anticoagulation activities ( 72 ). In regard to recent studies, we confirmed that FCS9-18 oligomers have antithrombotic activity without any adverse reaction because they might react with several blood coagulating proteins, and then, a majority of them could be discharged from the kidneys to protect against thrombosis; meanwhile, their total had nothing to do with hemorrhage, hypotension, and thrombocyte gathering through blood circulation ( 73 ).…”
Section: Polysaccharidessupporting
confidence: 75%
“…One experiment indicated that even if the patterns of sulfation differed, chondroitin sulfate obtained similar antithrombotic activity; thus, the influence of the chondroitin sulfation pattern could be less than the molecular weight with regard to the antithrombosis and anticoagulation activities ( 72 ). In regard to recent studies, we confirmed that FCS9-18 oligomers have antithrombotic activity without any adverse reaction because they might react with several blood coagulating proteins, and then, a majority of them could be discharged from the kidneys to protect against thrombosis; meanwhile, their total had nothing to do with hemorrhage, hypotension, and thrombocyte gathering through blood circulation ( 73 ).…”
Section: Polysaccharidessupporting
confidence: 75%
“…It is reported that high-molecular-weight FG can potently activate the plasma contact system and cause hypotension in rats, similar to OSCS [ 13 , 14 , 16 ]. Herein, the in vivo effect of TaFG, HfFG, and their depolymerized products were studied.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a natural FG from Thelenota ananas (TaFG) exhibited weaker in vivo antithrombotic activity than its depolymerized product in a stasis-induced venous thrombosis rat model [ 7 ]. Native FGs from Ludwigothurea grisea , Isostichopus badionotus , and Pearsonothuria graeffei could cause obvious hypotension and reduced heart rate in rats after intravenous injection [ 13 , 14 ]. However, the underlying mechanism is not clear, and how the undesired activities of FG are related to its in vivo toxicology remains to be studied.…”
Section: Introductionmentioning
confidence: 99%